2015
DOI: 10.1007/s11999-014-4046-3
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Difference in Total Knee Arthroplasty Risk of Revision in Highly Crosslinked versus Conventional Polyethylene?

Abstract: Background Highly crosslinked polyethylene (HXLPE) was introduced to reduce wear and associated osteolysis in total knee arthroplasty (TKA). However, there is limited clinical evidence that HXLPE is more effective than conventional polyethylene (CPE) in TKA. Questions/purposes (1) Do primary TKAs with HXLPE tibial inserts have a lower risk of revision (all-cause, aseptic, and septic) than TKAs with CPE tibial inserts? (2) In NexGen TKA (Zimmer Inc, Warsaw, IN, USA) bearings, do HXLPE tibial inserts have a lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 20 publications
2
6
0
1
Order By: Relevance
“…In this study, 18% (177/999) of primary knee explant records cited infection as the reason for retrieval. We also observed that PJI accounted for a larger fraction of explanted revision components, which is again consistent with the clinical literature [4], [13], [14], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, 18% (177/999) of primary knee explant records cited infection as the reason for retrieval. We also observed that PJI accounted for a larger fraction of explanted revision components, which is again consistent with the clinical literature [4], [13], [14], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31].…”
Section: Discussionsupporting
confidence: 91%
“…TKA and UKA declined in late revisions resulting from polyethylene wear/breakage, which also was found by Thiele et al [70]. Paxton et al [56] found a similar risk of revision for highly crosslinked polyethylene compared with conventional polyethylene. Highly crosslinked polyethylene is rarely used in Norway in knee arthroplasty (8% in 2013-2015) [69], indicating improvements in conventional polyethylene and polishing, sterilization, and locking mechanisms [37,39,68].…”
Section: Changes In Revision Causessupporting
confidence: 66%
“…At a mean of 6 years postoperatively, the HXLPE showed no significant differences in revision rates compared with the conventional PEs cohort at 7 years postoperatively. Furthermore, Paxton et al 6 did not find significant differences in revision rates between conventional and XLPE at 5-year follow-up (n ¼ 71,889 knees).…”
Section: Re-melted Highly Cross-linked Polyethylenementioning
confidence: 87%